Pengaruh Pemberian Terapi Musik Klasik Beethoven Terhadap Tingkat Kecemasan Pasien Pre Operasi Odontektomi - Vi Paradise Diputera; Amin Susanto; Asmat Burhan (Universitas Malahayati Lampung, 2025)
ABSTRACT Preoperative anxiety is a common problem that patients often experience before undergoing surgery, including odontectomy procedures. This anxiety can negatively affect the patient's physiological and psychological condition, as well as the postoperative recovery process. Classical music therapy, especially Beethoven's works, is believed to have a relaxing effect and can reduce anxiety levels. Objective: To determine the effect of Beethoven classical music therapy on the anxiety level of pre-operative odontectomy patients at Gunung Jati General Hospital, Cirebon City.Method: This study is a quantitative study with a pre-experimental design using a one group pretest-posttest approach. The sample consisted of 50 patients selected by total sampling technique. The instrument used was the APAIS (Amsterdam Preoperative Anxiety and Information Scale) questionnaire to measure anxiety levels before and after the intervention.Results: The results showed that before being given music therapy, the majority of patients experienced moderate anxiety (66%). After the intervention of Beethoven classical music therapy for 10 minutes, the anxiety level decreased significantly to mild anxiety (84%) and no anxiety (16%). Statistical tests showed a significant difference between anxiety levels before and after the intervention (p 0.05). Conclusion: Beethoven classical music therapy is effective in reducing the anxiety level of pre-operative odontectomy patients. This therapy can be used as a non-pharmacological intervention in anesthesia nursing practice to improve patient comfort. Keywords: Classical Music Therapy, Beethoven, Anxiety, Preoperative, Odontectomy ABSTRAK Kecemasan pre-operatif merupakan masalah umum yang sering dialami pasien sebelum menjalani tindakan pembedahan, termasuk prosedur odontektomi. Kecemasan ini dapat berdampak negatif terhadap kondisi fisiologis dan psikologis pasien, serta proses pemulihan pasca operasi. Terapi musik klasik, khususnya karya Beethoven, diyakini memiliki efek relaksasi dan mampu menurunkan tingkat kecemasan. Tujuan: Mengetahui pengaruh pemberian terapi musik klasik Beethoven terhadap tingkat kecemasan pasien pre-operatif odontektomi di RSD Gunung Jati Kota Cirebon.Metode: Penelitian ini merupakan penelitian kuantitatif dengan desain pra-eksperimen menggunakan pendekatan one group pretest-posttest. Sampel terdiri dari 50 pasien yang dipilih dengan teknik total sampling. Instrumen yang digunakan adalah kuesioner APAIS (Amsterdam Preoperative Anxiety and Information Scale) untuk mengukur tingkat kecemasan sebelum dan sesudah intervensi.Hasil: Hasil penelitian menunjukkan bahwa sebelum diberikan terapi musik, mayoritas pasien mengalami kecemasan sedang (66%). Setelah intervensi terapi musik klasik Beethoven selama 10 menit, tingkat kecemasan menurun secara signifikan menjadi kecemasan ringan (84%) dan tidak ada kecemasan (16%). Uji statistik menunjukkan adanya perbedaan signifikan antara tingkat kecemasan sebelum dan sesudah intervensi (p 0,05).Kesimpulan: Terapi musik klasik Beethoven efektif dalam menurunkan tingkat kecemasan pasien pre-operatif odontektomi. Terapi ini dapat dijadikan intervensi non-farmakologis dalam praktik keperawatan anestesi untuk meningkatkan kenyamanan pasien. Kata Kunci: Terapi Musik Klasik, Beethoven, Kecemasan, Pre Operasi, Odontektomi